Spatiotemporal Variation Characteristics and Influencing Factors of Water Transparency in the Pilot Zone of Yangtze River Delta - WANG Yu, ZHOU Wei-qi, BAI Meng-yu, SU Han, HU Wei (长江科学院院报)
[Objective] This study focuses on typical water bodies (lakes, rivers inside the polder area, and rivers outside the polder area) in the pilot zone of the Yangtze River Delta, aiming to: (1) analyze the spatiotemporal differentiation characteristics of water transparency (Secchi Depth,SD) in the three typical water bodies; (2) identify the key drivers of SD through correlation and regression models; (3) propose SD improvement thresholds based on the light compensation requirements of submerged vegetation restoration, providing scientific evidence for precise water quality management in plain river networks. [Methods] The study was based on field monitoring data from April to December 2023, focusing on water transparency and other water quality indicators in the Pilot Zone. The analysis combined trends in monthly variations of suspended solids (SS), total phosphorus (TP), chlorophyll-a (Chl-a), and turbidity to explore the spatiotemporal distribution and variation characteristics of SD. Correlation analysis and curve fitting models of SD with turbidity, SS, and TP were employed to quantify the driving mechanisms of SD. Based on the survival needs of local nearshore submerged vegetation, SD thresholds and strongly related water quality improvement targets were established. [Results] (1) River channels within embankments exhibited the highest average SD (68.75 cm), but fluctuated significantly due to rainfall disturbances. The seasonal difference in lake SD was significant (average 61.17 cm), with peak values in winter (80.14 cm) and minimum values in summer (48.00 cm). River channels outside embankments had the lowest SD (45.08 cm) due to strong hydrodynamic disturbances from navigation. Spatially, SD exceeded 70 cm in the southeast of Xitang Town and Lili Town, while SD was below 50 cm in Yuandang Lake, the northeast of Jinze Town, and Taipu River due to aquaculture pollution, construction runoff, and resuspension of bottom sediment. (2) SS concentration was the primary correlated indicator of SD (R=-0.65 to -0.79). The negative correlation between TP and SD was particularly significant in lake water (R=-0.71), and the C3 component (humic-like substances) of dissolved organic matter (DOM) shared a common origin with TP (R=0.64), indicating that TP in lake water mainly originated from soil erosion and surface runoff input. In river channels within embankments, there was no significant correlation between Chl-a and SD (R=-0.14), and Chl-a exhibited the lowest concentration (4.45 μg/L), attributed to the algae-suppressing effect of dense submerged plant growth. (3) SD in channels within embankments was significantly affected by heavy rainfall (73.90 mm in June), with a 20%-40% decrease, while SS (↑60 mg/L) and TP (↑0.12 mg/L) levels significantly increased. However, weak rainfall (≤46.93 mm) had a relatively insignificant effect on water transparency. (4) To maintain local submerged vegetation in the pilot zone, SD should be maintained above 59.14-83.06 cm (calculated based on light compensation depth), corresponding to the following thresholds for strongly correlated water quality indicators: turbidity (Turb) ≤7.46-16.14 NTU (for all water bodies), SS≤18.42-43.41 mg/L (for river channels outside embankments), and TP≤0.052-0.099 mg/L (for lakes). [Conclusion] Recommendations are proposed for future transparency enhancement projects in the pilot zone: for lakes, control land-based phosphorus input; for river channels outside embankments, enhance bottom sediment stabilization under navigation disturbances; for river channels within embankments, emphasize the algae-suppressing function of submerged vegetation, highlighting the synergistic effect of ecological restoration on transparency management.